2007
DOI: 10.1051/0004-6361:20066956
|View full text |Cite
|
Sign up to set email alerts
|

Minkowski's footprint revisited

Abstract: Context. M 1-92 can be considered an archetype of bipolar pre-planetary nebulae. It shows a clear axial symmetry, along with the kinematics and momentum excess characteristic of this class of envelopes around post-AGB stars. Aims. By taking advantage of the new extended configuration of the IRAM Plateau de Bure interferometer, we wanted to study the morphology and velocity field of the molecular gas better in this nebula, particularly in its central part.Methods. We performed sub-arcsecond resolution interfero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 14 publications
9
81
0
3
Order By: Relevance
“…Other values are found from a dust shell model assumed by De Ruyter et al (2005), who found R in = 22 mas and R out = 397 mas. Alcolea & Bujarrabal (1991) also fitted the extended emission with a shell model and found R in = 76 mas and R out = 3330 mas with a dust temperature of T = 360 K. We can also note that AC Her was studied using high-resolution imaging with adaptive optics by Close et al (2003), who did not detect any extended mid-infrared structure larger than 200 mas.…”
Section: Ac Hermentioning
confidence: 75%
See 1 more Smart Citation
“…Other values are found from a dust shell model assumed by De Ruyter et al (2005), who found R in = 22 mas and R out = 397 mas. Alcolea & Bujarrabal (1991) also fitted the extended emission with a shell model and found R in = 76 mas and R out = 3330 mas with a dust temperature of T = 360 K. We can also note that AC Her was studied using high-resolution imaging with adaptive optics by Close et al (2003), who did not detect any extended mid-infrared structure larger than 200 mas.…”
Section: Ac Hermentioning
confidence: 75%
“…The case of R Sct is peculiar and this star is often classified as an exception by several authors. Alcolea & Bujarrabal (1991) used a two shell model to interpret both its mid-IR and far-IR data and estimated a temperature for the largest grains of T = 815 K. The estimated radii of the shells were R in,1 = 30 AU, R out,1 = R in,2 = 5 720 AU, and R out,2 = 12 000 AU (using d = 431 pc), where the indices 1 and 2 denote the inner and outer shells, respectively. We possibly detected the emission of the inner shell from our VISIR photometry but no spatially extended emission larger than R = 100 AU.…”
Section: Discussionmentioning
confidence: 99%
“…A second important effect that affects the location of the data points in Figure 1 is uncertainty in the inclination angles of the Bujarrabal et al 1998;(8) Alcolea et al 2007;(9) Castro-Carrizo et al 2002;(10) Huggins et al 2004;(11) Riera et al 2003;(12) Hirano et al 2004; (13) jets and tori. The adopted values and estimates of the uncertainties are given in the Appendix.…”
Section: Near Simultaneitymentioning
confidence: 99%
“…Planetary nebulae ( PNe) are observed to exhibit remarkably complex morphologies that are not well understood (e.g., Balick & Frank 2002;Meixner et al 2004). Point symmetry is the most striking characteristic of the nebulae and is known to be produced by the action of high-velocity jets which emanate from the central star system and interact with the circumstellar gas.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, an important development has been the ability to map the CO emission of individual objects in more detail (e.g., Cox et al 2000;Alcolea et al 2007). Together with HST imaging (e.g., Sahai et al 2007) a standard picture has emerged of a typical pre-PN.…”
Section: Introductionmentioning
confidence: 99%